Communication network of the Ararat Plain, Armenia. Geographical, economic, political dimensions (1st millennium BC – 1st millennium AD) - Zardaryan , Mkrtich H. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
Ararat Valley – the largest plain of the Armenian Highlands, at least since the stage of Chalcolithic takes up the role of the economic and cultural centre of the mentioned region. This phenomenon was the naturally determined result of the climatic and orographic characteristics of the valley and particularly its communicative characteristics. The latter was mostly based on the river-lines of the valley itself, as well as the network of adjacent river drainages and the accessible mountain passes. In course of time these natural ‘channels’ had facilitated the formation of roads at the axis of South-North and East-West (Arax – Hrazdan – Akhurian – Arpa – Vorotan – Kotur; Aghstev – Kur – Aragvi; Euphrates and Tigris water drainages etc.). In these aspects the interconnection of the societies with those of the neighboring regions is proven by the corresponding archaeological materials, which confirm both the facts of import and export. The economic, social and other processes of the following centuries resulted in the development of stable communication routes of the highlands and their active operation. Since at least the beginning of the 1st millennium BC, along with the establishment of unitary statehood on the territory of the Armenian Highlands (Urartu), the system of trade routes develops greatly, with Ararat Valley as one of its most important hubs. This route system has been inherited and enlarged by Armenian kingdoms of the subsequent, Classical period (Ervandid, Artaxian, Arsacid). Since the 6th century BC the trade routes of Armenia, and particularly the Ararat Valley, are tightly integrated into the road networks of the Near East, Central Asia and the Eastern Mediterranean. Thus, the following routes went through Ararat Valley: roads leading to the North – to the Eastern shore of the Black Sea and the mountain passes of the Caucasus; roads leading to the East, South and West – Iran, Mesopotamia, Syria and Asia Minor. The constant and active exploitation of all the mentioned routes finds its reflection both in narrative sources, as well as archaeological and numismatic materials. The same sources confirm the fact that the communication routes of the valley were also incorporated into the network of the Great Silk Road since the 2nd century BC up to the late Middle Ages. The fact that five of the six capitals of Classical and Early Medieval Armenia (Armavir, Ervandashat, Artashat, Vagharshapat, Dvin) have been located in Ararat Valley is the clear illustration of the economic, communicational, cultural and at last political importance of this sub-region of the Armenian Highland. The contemporary methods of Roadology, basing on the complex research of the geographic, narrative, archaeological and other data, provide an opportunity of revealing the line of these routes, the dynamics of their exploitation, the role of the trading centres located along these routes, the details of import and export etc.